Effectiveness of Kahoot as a revision tool in studying waves - Orillo, Jhoanne Catindig (Animo Repository, 2019)
This paper focused on the effectiveness of Kahoot, a game-based student response system, as a revision tool in studying waves. There were sixty-six G12 student participants from an all-boys school in Metro Manila Philippines. The students were all enrolled in SY 2016-2017 and came from different K-12 strands: Science Technology, engineering and Mathematics (STEM), Business, Administration and Management (BAM) and Humanities and Social Sciences (HUMSS). The students were grouped into two, one section (group A) used Kahoot during their revision in waves while the other group (group B) used the common way of revision in which teacher projects the items on the screen and wait for the students to answer each question. Both group of students had the same number of sessions and number of formative assessments in waves. Results showed that there is a significant difference in students' performance in terms of their summative test grades. Group A, who used Kahoot got a significantly higher summative test grades than Group B. In terms of students' perception with the use of Kahoot as a revision tool in studying waves, results showed that most students: 1) had fun during the game; 2) agree that they learned something from the game; 3) said that they will recommend the game; and 4) felt positive after the game. Results also revealed that the performance of the students in the summative test is largely associated with their perception of learning and feeling.